Asthma: an epidemic caused by epigenetics? - Schwartz, David (Henry Stewart Talks, 2011)
Genetic and biological determinants of diseases influenced by the environment, Epigenetics, Epigenetic mechanisms can be influenced by environmental exposures and aging, Histone modifications and innate immunity, Asthma is a major public health problem, Epigenetics and airway immunology, DNA methylation changes and asthma, Runx3 and airway disease, In utero folate supplementation and asthma, Sib pair asthma study, Preliminary analysis, Global methylation patterns: asthmatics vs. nonasthmatics, Hypomethylation of GATA3 or MUC5B is associated with asthma in concordant sib pairs, Hypermethylation of NOS2 is associated with concordant asthma, Asthma: an epidemic caused by epigenetics?
Reviewed at 2020/10/11